Young Learners’ Regulation of Practice Behavior in Adaptive Learning Technologies - Molenaar, Inge; Horvers, Anne; Dijkstra, Rick (Frontiers in Psychology, 2019)
Although research indicates positive effects of Adaptive Learning Technologies on learning, we know little about young learners’ regulation intentions in this context. Learners’ intentions and self-evaluation determine the signals they deduce to drive self-regulated learning. This study had a twofold approach as it investigated the effect of feed-up and feed-forward reports on practice behaviour and learning and explored learners’ self-evaluation of goal-attainment, performance and accuracy. In the experimental condition, learners described their goals and self-evaluated their progress in feed-up and forward reports. We found no conclusive effects of the feed-up and forward reports on learners’ regulation of practice behaviour and learning. Furthermore, results indicated that young learners’ self-evaluations of goal attainment and performance were biased. Contrary to other research, we found learners both over- and underestimated performance which was strongly associated with over- or underestimation of goal attainment. Hence the signals learners used to drive regulation were often incorrect, tending to induce over- or under-practising. Similarly, we found a bias in self-evaluation of accuracy and accuracy attainment. Learners over- or underestimated their accuracy, which was associated with over- or underestimation of accuracy attainment, which may in turn have affected effort regulation. We concluded that goal setting and self-evaluation in feed-up and forward reports was not enough to deduce valid regulatory signals. Our results indicate that young learners needed performance feedback to support correct self-evaluation and to correctly drive regulatory actions in ATLs.